Antara AI, Manusia dan Kegiatan Agama - Faisyal . (Oratio Directa (Prodi Ilmu Komunikasi), 2023)
Abstraction Not only does it enter the public space, AI technology also enters the private sphere and human religious activities. Many forms of religious activities are now help by AI. Some religious stakeholders have already used AI in worship services. There has been a change in the pattern of human worship, previously using the role of religious leaders such as priests, ustadz or biksu, now that role is being taken over by AI. If this continues for a long time, the presence of AI can gradually replace religious leaders, and there will be a change in the relationship between religious leaders and congregations. The quality of the relationship between humans and God can decrease, because not relation psychology between AI with human and God. Keywords: Artificial intelligence, humans, religion